Study of fractal bond connectivity of neodymium phosphate glasses by ultrasonic technique - Budi, Agus Setyo; Hussin, Rosli; Sahar, Md. Rahim (Penerbit UTM Press, 2002)
The elastic properties of neodymium phosphate xNd2O3(1-x)P2O5 glasses with different compositions containing from 10 to 25 mole % Nd2O3 has been studied by ultrasonic technique, as functions of temperature from 270 K to 303 K. The elastic properties like adiabatic elastic stiffness coefficients, C11, C44 and bulk modulus, B of the glasses have been determined using the experimental data. The temperature dependence of the elastic properties were used to explores useful information about the fractal bond connectivity of the neodymium phosphate glasses which lies between 2.00 and 2.70. This result indicates that the neodymium phosphate glasses were connected in an array between two and three dimensional network.